The Great Timber Roof of Porta Nuova Railway Station in Turin: The Role of Assessment and Diagnosis for Sustainable Repair and Conservation. Issue 1 (2nd January 2019) - Bertolini-Cestari, Clara; Brino, Giovanni; Cestari, Luciana; Crivellaro, Alan; Marzi, Tanja; Pignatelli, Olivia; Rolla, Steni; Violante, Alberto
ABSTRACT: This article illustrates a wide multidisciplinary project carried out as part of recent restoration works of the great timber roof of Porta Nuova Railway Station in Turin (Italy). The station was built in 1861 (project by A. Mazzucchetti and A. Castigliano), when Turin was the first capital of Italy. In recent years, the roof needed important maintenance and restoration interventions due to water leaking which caused the decay of the timber structure. The original roof was under threat also because there was a proposal for the complete substitution of the timber elements (in a total of 2350 m 2 ). However after accurate assessment and diagnosis (following recent regulations) it was possible to save the original timber structure and to plan and realize sustainable interventions for repair and conservation with innovative technologies. This was carried out within a complex restoration site of the whole building.